Systematic Eco-innovation in Lean PSS Environment - Pacheco, Diego A De J (2017)
New methodologies and tools to improve the performance of PSS design have been proposed in literature. In this sense, this paper accompanies the development of a proposed model that allows for systematic analysis in order to identify waste or contradictions and their elimination or reduction, through the joint use of analytical tools wit impact in eco-innovation based on TRIZ and Lean PSS. It has been shown that the methodologies complement each other. The TRIZ with its aspect of innovation and problem solving can make an important contribution in the eco-innovation in a Lean PSS design aiming application in real systems.